Avances de investigacion sobre asociados en el CRI Carmen de Bolivar - Arrieta B., J.M. (International Center for Tropical Agriculture, 1990)
The main results of research on different intercropping systems, including tobacco//cassava and yam x maize//cassava, are detailed. When cassava is intercropped with tobacco, tobacco yields are reduced by 24.3 percent but quality characteristics of leaves and no. of leaves/plant/harvest are not affected. Yields of 8.9 t/ha are reported for cassava, similar to those obtained in monoculture. In yam x maize//cassava, yam yields were lower that regional av.; cassava yields were higher at greater planting distances. Further studies are recommended with planting distances of 1.2 x 1.0, 1.2 x 1.2, 1.5 x 1.2, and 1.5 x 1.0 m, planting systems in which cassava yielded 7.8, 6.1, 8.3, and 6.8 t/ha, resp. The new trials established at the on-farm level and at the Centro Regional de Investigacion El Carmen are listed. (CIAT)